PENINGKATAN MUTU MI KERING JAGUNG DENGAN PENERAPAN KONDISI OPTIMUM PROSES DAN PENAMBAHAN MONOGLISERIDA [Quality Improvement of Dried Corn Noodle through the Optimization of Processing Conditions and Addition of Monoglyceride] - . Subarna; Tjahja Muhandri; Budi Nurtama; Antung Sima Firlieyanti (Jurnal Teknologi dan Industri Pangan, 2012)
The objective of this research was to improve the quality of dried corn noodle through the optimization of processing condition using a cooking-forming extruder and the addition of monoglyceride. The process conditions was optimized using Response Surface Methodology (RSM) based on two processing parameters i.e., extruder temperatures (80-90°C) and screw speeds (75-125 rpm). The optimum condition of cooking extrusion was obtained at 90°C and 75 rpm. However, the noodle firmness and stickiness were unsatisfactory. The use of 1% Glyseryl Mono Stearate significantly improved the quality of the noodle with acceptable firmness, elasticity, and elongation. However, the cooking loss and stickiness were still high.